Vertical Mandibular and Trunk Symmetry in Indonesian Orthodontic Patients - Ervina Sofyanti; Elza Ibrahim Auerkari; Trelia Boel; Benny M. Soegiharto (Association of Support to Oral Health Research (APESB), 2021)
Objective: To analyze differences in vertical mandibular and trunk symmetry in orthodontic patients. Material and Methods: This was a cross-sectional study of 129 growing orthodontic patients who sought orthodontic treatment at the Dental Hospital Universitas Sumatera Utara, Indonesia. Mandibular symmetry index was observed with pre-treatment panoramic radiography based on Kjellberg's technique and trunk symmetry was evaluated based on questionnaires and visual observation. Vertical mandibular asymmetry was decided if the index of asymmetry was lower than 93.7%. The bivariate analysis used the chi-squared and Fisher's exact tests, with a significance level of 5%. Results: There was a significant association between vertical mandibular and trunk symmetry (p<0.05). The prevalence odds ratio for the association with vertical mandibular asymmetry was 3.007 (95% CI = 1.016-8.905) for trunk asymmetry. Conclusion: The necessity to consider trunk symmetry could be included in orthodontics treatment of any malocclusion with vertical mandibular asymmetry that might require a multidisciplinary approach in the future.